2021
DOI: 10.1002/jcla.23778
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of urine heat shock protein 70 and prostatic exosomal protein in chronic prostatitis

Abstract: Objective To explore the diagnostic value of the levels of prostatic exosomal protein (PSEP) and heat shock protein 70 (HSP70) in the urine of patients with chronic prostatitis (CP). Method Urine samples from 210 CP patients (70 cases of the USA National Institutes of Health Category II [NIH‐II], 70 NIH‐IIIa, and 70 NIH‐IIIb patients) and 70 control subjects were collected between May 2018 and February 2020. The levels of PSEP and HSP70 in urine were detected by enzyme‐linked immunosorbent assay. The differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The results showed the presence of the Hsp70 protein in all the samples analyzed. This correlates with other authors who have shown that Hsp are constitutively and ubiquitously expressed in eukaryotic cells, where they participate in the maintenance of cell function [56] [57].…”
Section: Discussionsupporting
confidence: 92%
“…The results showed the presence of the Hsp70 protein in all the samples analyzed. This correlates with other authors who have shown that Hsp are constitutively and ubiquitously expressed in eukaryotic cells, where they participate in the maintenance of cell function [56] [57].…”
Section: Discussionsupporting
confidence: 92%